Controlled nanonization of poorly water-soluble drugs for reliable bioavailability - Lee, Beom Jin (IFMBE Proceedings, 2018)
Solid dispersions (SD) can be utilized to improve the dissolution rate of poorly water-soluble drugs and further to modulate the release pattern by selecting an appropriate hydrophilic polymer. SD overcomes the many solubility issues of various types of poorly water-soluble drugs, providing the medical benefits to obtain a reliable bioavailability. Controlled release (CR) systems offer several medical advantages, such as reducing the adverse effects, dosing frequency and ultimately enhancing the patient compliance. Thus, SD-loaded CR (SD-CR) systems provide some privileges in drug delivery by taking into consideration of solubilization and controlled release of poorly water soluble drugs for optimal therapy.
Keywords: Controlled release; Dissolution rates; Dosing frequency; Hydrophilic polymers; Nanonization; Patient compliance; Poorly water-soluble drugs; Solid dispersion; Classification of solid dispersions; Controlled release solid dispersion; Nanonization; Poorly water-soluble drugs; Solubilization mechanism